The Influence of Interpersonal Communication and Self-Efficacy on Performance with Growth Mindset as a Moderation - Hansen Wilando; Meiliani Sujarwo; Andika Prawira (Komunitas Dosen Indonesia, 2024)
Companies face Lots challenges and needs employees who have good performance, ability interpersonal communication, and efficacy self. Beside Therefore, it also requires employees who have growth mindset so that help company for move to direction progress. Study This aim for know influence interpersonal communication and efficacy self to performance, as well know impact moderation growth mindset to interpersonal communication, efficacy self and performance. Methods used in research This is Structural Equation Modelling with help Smart PLS Software. Method Hair used for determine amount sample, and 152 respondents produced. Study This addressed to employees who work in the city and district of Tangerang. Research result show that interpersonal communication and efficacy self-influential in a way direct to performance, as well moderation growth mindset influential significant among interpersonal communication and efficacy self to performance. Implications from study This If company want to increase performance, then priority strategy is with prioritize growth mindset.